2015
DOI: 10.1371/journal.pone.0115639
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging and Characterization of Actin Microridges

Abstract: Actin microridges form labyrinth like patterns on superficial epithelial cells across animal species. This highly organized assembly has been implicated in mucus retention and in the mechanical structure of mucosal surfaces, however the mechanisms that regulate actin microridges remain largely unknown. Here we characterize the composition and dynamics of actin microridges on the surface of zebrafish larvae using live imaging. Microridges contain phospho-tyrosine, cortactin and VASP, but not focal adhesion kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 43 publications
14
97
0
Order By: Relevance
“…The two "classical fingerprint" patterns are overall similar to microridge patterns described in many studies (e.g., Hawkes, 1974;Anderson 1976, Fishelson, 1984. A recent study of microridge dynamics in zebrafish embryos (Lam et al, 2015) showed that prior to and during cytokinesis, the microridges disassemble into actin-based puncta or small ridges which later reform into microridges after completion of cell division. The second classical fingerprint pattern (classical II) is reminiscent of the first but consists of more tightly packed, virtually parallel ridges but with no obvious cross-bridging structures (Figure 2b), and was infrequently found.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The two "classical fingerprint" patterns are overall similar to microridge patterns described in many studies (e.g., Hawkes, 1974;Anderson 1976, Fishelson, 1984. A recent study of microridge dynamics in zebrafish embryos (Lam et al, 2015) showed that prior to and during cytokinesis, the microridges disassemble into actin-based puncta or small ridges which later reform into microridges after completion of cell division. The second classical fingerprint pattern (classical II) is reminiscent of the first but consists of more tightly packed, virtually parallel ridges but with no obvious cross-bridging structures (Figure 2b), and was infrequently found.…”
Section: Discussionsupporting
confidence: 76%
“…Phosphorylation of tyrosine is a hallmark of signal transduction via protein tyrosine kinases (PTKs) and phosphatases (PTPs). EGFP-VASP localized to the microridges of embryonic zebrafish epidermis along with tyrosine-phosphorylated proteins (Lam et al, 2015), the latter which were present at constitutively high enough levels to be detected without PTP inhibition. The accumulation of phosphotyrosine antibody after PTP inhibition indicates PTKs and PTPs are active components of microridges under native conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However some species had only microvillous structures on the body surface in earlier stages, indicating a progression to the microridge structures of later embryos. Previous studies have indicated that microvillous structures are assembled into the mature ridges (Gorelik et al, ; Lam et al, ). The former study in particular showed microridge elongation occurred through the lateral association of newly formed actin‐based microvilli with the microvillous cores of pre‐existing ridges.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the patterns of microridges of juvenile and adult sea bass (Dicentrachus labrax) were described by El–Bakry (), where a more complex, twisting arrangement of ridges was found in the adult. Lam et al () noted a progression from simple to more complex microridge patterns in developing zebrafish embryo epidermis, suggesting there is a relationship between developmental stage and extent of ridge pattern complexity. Two other studies dedicated to microridges during early teleost development are that of Foscarini () and Panhuis, Fris, Tuhela, and Kwan (), both of which carried out extensive SEM surveys of epithelial surface structures and described a transition from microvillous surface projections to microridge formations.…”
Section: Introductionmentioning
confidence: 99%